T Cell-Derived Protein S Engages TAM Receptor Signaling in Dendritic Cells to Control the Magnitude of the Immune Response - Carrera Silva, Eugenio Antonio (2013)
Dendritic cell (DC) activation is essential for the induction of immune defense against pathogens, yet needs to be tightly controlled to avoid chronic inflammation and exaggerated immune responses. Here, we identify a mechanism of immune homeostasis by which adaptive immunity, once triggered, tempers DC activation and prevents overreactive immune responses. T cells, once activated, produced Protein S (Pros1) that signaled through TAM receptor tyrosine kinases in DCs to limit the magnitude of DC activation. Genetic ablation of Pros1 in mouse T cells led to increased expression of costimulatory molecules and cytokines in DCs and enhanced immune responses to T cell-dependent antigens, as well as increased colitis. Additionally, PROS1 was expressed in activated human T cells, and its ability to regulate DC activation was conserved. Our results identify a heretofore unrecognized, homeostatic negative feedback mechanism at the interface of adaptive and innate immunity that maintains the physiological magnitude of the immune response.